Antenatal corticosteroid therapy modulates hepatic AMPK phosphorylation and maternal lipid metabolism in early lactating rats - Fernanda Ballerini Hecht (Elsevier, 2021)
Antenatal corticosteroid therapy is used to reduce neonatal mortality in preterm infants but it is currently unknown whether this intervention affects lipid metabolism at the peripartum. This study aimed to evaluate if antenatal corticosteroid therapy in pregnant rats and women affects lipid metabolism during early lactation. We evaluated women at risk of preterm delivery that received corticosteroid therapy (CASE) and women that were not exposed to corticosteroid and were not at risk of preterm delivery (CONTROL). Samples were collected to measure serum and milk triacylglycerol (TAG) three days after delivery. Rats were treated with dexamethasone (DEX) between the 15th and the 20th days of pregnancy. Samples were collected at different days after delivery (L3, L8 and L14). TAG was measured in serum, liver and mammary gland (MG). TAG appearance rates were measured after tyloxapol injection and gavage with olive oil. We also evaluated the expression of key genes related to lipid metabolism in the liver and in the MG and hepatic phosphorylation of AMP-activated protein kinase (AMPK) and acetyl-CoA carboxylase (ACC). CASE volunteers delivered earlier than CONTROL but presented unaltered milk and serum TAG concentrations. Early lactating DEX rats exhibited increased TAG in serum, MG and milk. No changes in CD36 and LPL were detected in the MG and liver. Early lactating DEX rats displayed increased TAG appearance rate and reduced hepatic AMPK/ACC phosphorylation. Our data revealed that antenatal corticosteroid therapy reduces hepatic AMPK/ACC phosphorylation during early lactation that reflects in increased TAG concentration in serum, MG and milk.